Economic Reintegration: How Do Gumelar Migrant Workers Achieve Sustainable Economic Welfare? - Meutia Karunia Dewi; Novita Puspasari; Sofiatul Khotimah; Aldy Setiawan (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2022)
This research was held in Gumelar, one of the largest migrant communities in Central Java Province. The research was done by combining fieldworks and literature reviews to meet Gumelar migrant workers and the government perspective. Data was collected by using in-depth interviews and Focused Group Discussion (FGD) methods. The interviews conducted involved 10 family members of migrant workers and 14 former migrant workers. Meanwhile, in the three FGDs, there were 10 former PMIs (Indonesian Migrant Workers) involved and 6 PMI candidates. This qualitative research produces a Causative-Pathway Model for Migrant Labor Economic Reintegration. It was found that the social values upheld by the participants influenced their financial planning patterns. Meanwhile, based on a study of various official media, there were three potential government supports related to PMI's economic reintegration in the form of policies and systems related to three domains. They are: financial planning, job opportunities and business opportunities.